A gestão de relacionamentos em ambientes organizacionais multiculturais pela visão do aluno de relações públicas - Lima, Isabella Pinto de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This final report presents the results of scientific initiation research sought to understand the public relations student view of Unesp Bauru about one of the main functions of this professional, which is the management of relationships and the study of multiculturalism. The correlation of these concepts was analyzed by theoretical studies followed by the development, implementation and analysis of two surveys conducted with classes of 1 to 4 year course, to understand the student's vision as a professional future of public relations. For a wide-ranging understanding, it was initially conducted a quantitative survey with all students of the course, with direct questions and sought to identify the different profiles within the course. Then a qualitative research, with a smaller number of participants, sought to study and know in depth the profiles found in the first survey. Thereafter an analysis of each survey was conducted separately and, finally, an overall analysis was done, generating the final completion of work that seeks to finally understand how the student's public relations Unesp Bauru sees the importance of relationship management in multicultural organizational environments, and beyond, whether he understands that multiculturalism is a determining factor in the manager's work and vice versa. From the collected information and the reflection from the developed theoretical foundation it was understood that the course students do not have proximity to the theme and recognize this failure, but also understand the need to deepen the content because of their relevance in the marketing environment and academic

Este relatório final apresenta os resultados da pesquisa de iniciação científica que buscou entender a visão do aluno de relações públicas da Unesp Bauru a respeito de uma das principais funções desse profissional, que é a gestão de relacionamentos e o estudo da multiculturalidade e da interculturalidade. A correlação desses conceitos foi analisada por meio de estudos teóricos seguidos da elaboração, aplicação e análise de duas pesquisas realizadas com as turmas do 1º ao 4º ano da Unesp visando compreender a visão do aluno enquanto futuro profissional de relações públicas. Para um entendimento de amplo alcance, foi realizada inicialmente uma pesquisa quantitativa com todos os alunos do curso, com perguntas diretas e que buscou identificar os perfis variados dentro do curso. Em seguida, uma pesquisa qualitativa, com um número menor de participantes, buscou estudar e conhecer a fundo os perfis encontrados na primeira pesquisa. A partir dos dados coletados e da reflexão a partir da fundamentação teórica desenvolvida compreendeu-se que os alunos do curso não têm proximidade com a temática e reconhecem essa falha, porém entendem a necessidade de aprofundamento no conteúdo devido a sua relevância no meio mercadológico e acadêmico
Keywords: Relações publicas; Multiculturalismo; Cultura; Culture